Learning Management Strategies to Improve the Quality of Education in Senior High School - Muttaqin, Faiz Zainal; Khasanudin, M.; Sariman, Sariman (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The more study describes the implementation of learning management in SMA Al Muhammad Cepu, the approach used is descriptive qualitative through case study research. Where the researcher is directly involved in extracting information from a phenomenal event regarding learning in the location. The principal, Deputy Principal for Curriculum, and teachers of SMA Al Muhammad Cepu as subjects in the current study. It was found that learning management: learning management abilities of SMA Al Muhammad Cepu teachers in planning aspects were carried out through an IHT review of lesson planning, increasing reading literacy from various reading sources in the library, attending training, seminars, and upgrading. At the same time, the teacher organizing section performs five learning steps: literacy activities, critical thinking, fulfilling adequate educational facilities and having relevance to learning needs, providing space and awards for outstanding teachers, by holding exceptional teachers, teacher creativity competitions, and promotions.